CAUGHT IN THE WEB OF THE LAW LE TRADUCTEUR JURIDIQUE FACE À LA MÉTAPHORE - HOUBERT, Frédéric (Comparative Legilinguistics, 2017)
Thin skull doctrine, living tree, blue-sky law, clean hands, cloud on title… Metaphors play a very important role in the English legal language. How can we explain the popularity of metaphors in legal langauge of common law? Metaphors help understand abstract concepts thanks to pictueresque and well known images. This function of metaphors will be discussed in this paper. Having reviewed two groups of metaphors in the English legal language (called in French les métaphores corporelles and les métaphores «naturelles»), the author thouches upon the problems connected with their translation. It is concluded that apart from the most popular translation method (adaptation of metaphors due to the more abstract nature of the French language), other translation may be applied as well including literal translation. The author analyzes certain metaphors in respect of which literal translation may be applied.